Murder at the Christmas Cookie Bake-Off - Hannah, Darci (Hannah, Darci. Beacon Bakeshop mystery, 2021)
"With the spirit of the holidays wafting through the Beacon Bakeshop, Lindsey thinks she has the recipe for the sweetest Christmas ever- winning the town-wide cookie bake-off. Unfortunately, striving for a picture-perfect December in Beacon Harbor is a lot like biting into stale shortbread. Low on staff and bombarded by visits from family, Lindsey can barely meet demands at work, let alone summon the confidence to face fierce competition . . . Self-appointed Christmas know-it-all Felicity Stewart is determined to take the top spot in the bake-off, and she's not afraid to dump a little coal in everyone's stocking to do it. Just as the competition heats up, everything falls apart when the judge is found dead- and covered in crumbs from Lindsey's signature cookie! Solving a murder was never on Lindsey's wish list. But with her reputation on the line during the happiest time of the year, she'll need to bring her best talents to the table in order to sift out the true Christmas Cookie culprit."--Back cover